Rural Tourism in Nepal: Opportunity and Challenges - Kafle, Dol Raj (HISAN: Journal of History Association of Nepal, 2022)
This study is focused on rural tourism in Nepal, including its opportunities and challenges. Rural areas, where the majority of Nepal’s population resides, have the potential to attract tourists and contribute to the country’s economic development. Involving the local people or villagers in the tourism industry can also increase the value of local products, culture, and traditions. However, there are also negative impacts of tourism on society, and it is important to carefully manage the industry to ensure a bright future for tourism in Nepal. The objective of this study is to examine the opportunities and challenges of rural tourism in Nepal.